(untitled) (Journal of Bio-Science, 2015)
Context: Coccinia Cordifolia Lin. is an important tropical vegetable and it belongs to the Cucurbitaceae family. The fruits of C. cordifolia as a rich source of different nutrients were analyzed. Objective: Studies were conducted to investigate the changes of nutritional compositions and hydrolytic and oxidative enzymes of C. cordifolia fruits at different maturity levels. Materials and Methods: The pH was measured by pH meter. The moisture and ash contents were determined by the method of AOAC. Total and water-soluble proteins were determined by the micro- Kjeldhal method and spectrophotometrically respectively. Lipid contents were determined by Bligh and Dyer. Total sugar and starch content were estimated by Anthrone method. Thiamin and riboflavin were estimated by Anonymous and ?-carotene was estimated by Jensen. Vitamin-C content was determined by the titrimetric method. Calcium, iron, sodium, potassium, cupper and magnesium content were determined by Atomic Absorption Spectroscopic method. Phosphorus was determined by colorimetric means. The protease and amylase activity were measured by Kunitz and Jayaraman respectively. Invertase activity was assayed by Mahadevan and Sridhar. Results: The pH was acidic. The moisture content decreased and ash content increased with age. Protein, total sugar, reducing sugar, lipid and vitamin contents increased rapidly while starch content decreased with maturation. Mineral contents increased up to the mature stage and decreased in ripen stage. The activity of amylase and invertase increased up to mature and thereafter decreased. Polyphenol oxidase and peroxidase activity were high in immature stage but decreased in matured stage and thereafter increased in ripen stage while the activity of protease and lipase increased all the maturity stage. Conclusion: In this study, ripen C. cordifolia fruits contained the highest amount of protein, total sugar, reducing sugar, ?-Carotene, vitamin B1, vitamin B2 and vitamin C whereas matured and immatured C. cordifolia fruits are rich sources of minerals and starch respectively. DOI: http://dx.doi.org/10.3329/jbs.v21i0.22517 J. bio-sci. 21: 35-41, 2013